“Hidden Patients” Family Caregivers of Elderly People with Dementia - สุทธิลักษณ์ ชยุตรา; อุไรเลิศ อัจฉรา; ชัชวาลย์ เนตรดาว; เทพนิมิตร ศุภรันยา (Journal of The Royal Thai Army Nurses, 2019)
Caring for the elderly people with dementia at home is a burden for family caregivers. The family caregivers have to face the progression of disease that become deteriorated in every day. When the elderly people with dementia are unable to perform daily activities and become more dependent, This situation causes difficulty in taking care of, especially family caregivers who do not have enough knowledge and have never been trained in caring. Moreover, family caregivers may have a physical illness that affects mental health. Therefore, the preparation for the family caregivers to take care of the elderly people with dementia and the caring for the family caregivers need to be provided based on holistic and individual care. When family caregivers are in good health. It will improve the quality of care for the elderly with dementia. This is an essential for the family caregivers who need to provide the best care to the elderly people with dementia in order to maintain good health and quality of life for both.